Interaksi Gaya Kepemimpinan Atasan terhadap Kinerja Guru-Guru Sekolah Islam Terpadu Khairul Imam, Medan (Studi Kasus : SMP IT Khairul Imam ) - Ikwan lubis (Universitas Katolik Widya Karya Malang, 2023)
The problems that exist at Khairul Imam IT Junior High School can be seen from the behaviour or attitude of its personnel, including teachers who are unable to do work based on the tasks and responsibilities that have been assigned. This tendency can be seen from the teachers' preference to accumulate or collect work. This research is conducted with inferential principles where the relationship between various variables tests hypotheses and makes generalisations. The population in this study were all teachers of SMPIT Khairul Imam, totalling 45 people. To determine the performance of SMPIT Khairul Imam teachers, the sampling procedure in this study used the saturated sampling method, namely the entire population (all teachers) who were used as respondents. This research data has 2 variables, namely the dependent variable is the performance of teachers (Y) and as an independent variable is the leadership style of superiors (X). In this study, it was found that the leaders at this research location have been able to carry out their functions well in directing, guiding, motivating, and supervising teachers to carry out their duties. All of that takes place because there has been interaction, communication and cooperation in the school environment. If the teacher has a good impression of the leader then the teacher will carry out the tasks that have been set with full seriousness and responsibility. So in this study it was concluded that the leadership style has an influence on the performance of Khairul Imam IT Junior High School teachers..